Elevating Indonesia's Performance in Ease of Doing Business Index (Policy Reforms to Improve the 'Starting a Business' Indicator) - Freddy, Imelda Magdalena; Saputri, N. (2018)
Indonesian President Joko Widodo has set a target of improving the country’s ranking in The World Bank’s Ease of Doing Business (EODB) index from 72nd to 40th by 2019. One barrier to meeting this challenge is Indonesia’s ranking in the Starting a Business Indicator, where it is 144th among 190 countries. According to the EODB Report, it takes 23 days and 11 procedures to register a business in Indonesia. To address this problem, the central government has implemented changes requiring parallel procedures with local governments and introduced a program called the Online Single Submission system (OSS), established in July 2018. However, there are major barriers to the success of these changes, including a lack of information for businesses, inadequate IT infrastructure, and failure to synchronize the central and local governments under the OSS. As a result, policy changes and the OSS have not been working as intended. Case studies in Jakarta, Bandung, and Bandar Lampung revealed that there are two regulations—one implemented by the local government and the other implemented by the central government—that should be revised to speed up business registration. The government should also remove a procedure from the business registration process and develop collaboration with local private sectors and business associations to improve the OSS. These changes would reduce the time required for registering a business by 17 days. These reforms would benefit small and medium businesses the most, since they are the most common types of business in Indonesia (approximately 98% of all businesses). Such a reduction in the time required to register a business would be enough to improve Indonesia’s Starting a Business Indicator ranking from 144th to 75th. Based on our findings, we recommend four policy changes. First, the Jakarta provincial government should revise the Regulation of the Head of Investment and One Stop Integrated Services 23/2017 Article 2d. The Mandatory Labor Affairs Report (MLAR) stipulated in this regulation should be removed as a business registration requirement. Its content is duplicates data provided by the BPJS Ketenagakerjaan documents as part of national social security program. In addition, requiring an MLAR contradicts the regulation of the Minister of Manpower (MOM) 14/2006, which says it is not required for business registration. Second, Government Regulation 24/2018 Article 78 should be reformed to require that the central government collaborate with local business associations to disseminate information about the OSS. This collaboration will ensure that information reaches even remote areas. Third, Government Regulation 24/2018 Article 88 should be reformed to ensure that the ministries related to the OSS assist local governments to synchronize standard operating procedures and regulations to implement the OSS. This assistance should continue for one year, after which there should be a penalty for local governments that fail to comply with the new procedures for registering businesses through the OSS. Fourth, Government Regulation 24/2018 Article 91 should be changed to ensure the government will collaborate with the private sector to improve the IT infrastructure in all regions to support the OSS. Participation by the private sector is important because they have the resources to provide internet access and computers needed to implement the OSS in districts and municipalities across Indonesia.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Políticas Públicas e Relações internacionais: Elementos endógenos e exógenos nas transferências do Orçamento Participativo na África - Porto de Oliveira, Osmany (Encontro Internacional: Participação, Democracia e Políticas Públicas: aproximando agendas e agentes, 2013)
Com cerca de 2500 casos no mundo, o Orçamento Participativo (OP) é um exemplo emblemático da proliferação em escala global das políticas de governança participativa. A literatura sobre o assunto avançou nas dinâmicas internas das experiências de OP. Todavia, ainda se conhece pouco sobre sua dimensão transnacional e as dinâmicas de circulação deste dispositivo de governança participativa. Este artigo se vale do estudo das relações internacionais e das análise de políticas públicas para preencher um vácuo na literatura. O objeto de pesquisa é a difusão do OP na África subsaariana, analisada à partir de suas dinâmicas regionais e de três casos representativos de transferência do OP na região. Este trabalho se fundamenta em informações coletadas in loco no Moçambique, na África do Sul e no Senegal.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - portuguese / português; budget / orçamento; ⛔ No DOI found

Translating the Idea of the eGovernment One-Stop-Shop in Indonesia - Wahid, Fathul (Springer, 2013)
This study aims to understand how the idea of an eGovernment one-stop-shop (OSS) has been translated into a new setting. Since the beginning of 2000, this idea has been implemented in a variety of ways by Indonesian local governments. Using an interpretive case study in the city of Yogyakarta, the study revealed that the specificity of each setting influences the translation process of the idea of OSS during its institutionalization. It also identified a set of editing rules used during the translation process. These include the editing rules concerning context (e.g., internal readiness); logic (e.g., corruption eradication); and formulation (e.g., standardized processes). The study also found that the idea translation was not a single round process.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA